Synthesis, Optical and Electrical Properties of PANI-MWCNT-ZnS Nanocomposites - Mrinmoy Goswami; Ranajit Ghosh; Ajit Kumar Meikap (Advanced Aspects of Engineering Research Vol. 11, 2021)
By in situ polymerization of aniline in the presence of MWCNT and negatively charged ZnS nanoparticles, polyaniline (PANI)-MWCNT-Zinc sulphide (ZnS) nanocomposites have been developed. HRTEM, FTIR, UV-VIS absorption spectroscopy, and photoluminescence (PL) spectroscopy were all used to classify the nanocomposites. Different nanocomposites’ particle diameters were determined to be around 3.21 nm using HRTEM. Absorbance measurements indicates that the incorporation of ZnS nanoparticles in PANI-MWCNT have occurred the red shift of band gap. Holstein model nonadiabatic small polaron model is applicable for these samples.